Rethinking solidarity in global society : the Challenge of Globalisation for Social and Solidarity Movements 50 Years after Bandung Asian African Conference 1955 - (:unkn) unknown (My University, 2007)
Within the context of the Cold War, the Bandung Spirit, expressed in 1955 by the African and Asian Countries was a call for peaceful coexistence, for independence from the hegemony of any superpower and for solidarities towards the weak and those being weakened by the world order of the day. It was an alternative to the hegemonic blocs, headed by the superpowers of the day, the US and the Soviet Union. Now, 50 years later, in the context of Globalisation, the world is still characterised by wars, similar systems of domination by the powerful and the continuous exploitation of the weak. Is there any alternative? Nineteen socially engaged intellectuals, academics and activists from Africa, Asia, Latin America, Europe, and USA, propose their reflections for an international collective work related to the commemoration of the 50th anniversary of Bandung Asian-African Conference 1955: Bernadette Andreosso O'Callaghan (France/Ireland), Bernard Founou-Tchuigoua (Cameroun/Senegal), Boutros Labaki (Lebanon), Darwis Khudori (Indonesia/France), Hersri Setiawan (Indonesia/Netherlands), Jean-Pascal Bassino (France/Japan), John Lannon (Ireland), Kaarina Kailo (Findland), Majid Tehranian (Iran/USA), Nirmal Kumar Chandra (India), Norman Mlambo (South Africa/Zimbabwe), Parichart Suwanbubbha (Thailand), Patricia Morales (Argentina/Netherlands/Belgium), Pierre Rousset (France), Rémy Herrera (France), Siti Musdah Mulia (Indonesia), Wolfgang R. Schmidt (Germany), Yukio Kamino (Japan), Yves Berthelot (France).
Keywords: African Research